2021
DOI: 10.3390/ma14185173
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Geometry and Infill Degree of Extrusion Additively Manufactured 316L Stainless Steel Components

Abstract: This study focuses on the effect of part geometry and infill degrees on effective mechanical properties of extrusion additively manufactured stainless steel 316L parts produced with BASF’s Ultrafuse 316LX filament. Knowledge about correlations between infill degrees, mechanical properties and dimensional deviations are essential to enhance the part performance and further establish efficient methods for the product development for lightweight metal engineering applications. To investigate the effective Young’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…However, Srinivasan et al report that the rectilinear pattern provides higher tensile properties than concentric [195]. From the Ultrafuse 316L metal MEX tensile properties reviewed in this work, the rectilinear with 45 • /90 • pattern with appropriate printing parameters (nozzle size, printing speed, strand width, layer thickness and first layer adjustment) reported by Moritzer et al [93] provides higher tensile properties than other infill patterns [66,98] and also similar infill patterns [53,57]. As reported by Singh et al [79], the 0 • /90 • zigzag infill pattern in metal MEX can also provide comparable tensile properties to MIM parts.…”
Section: Effects Of Printing Parameters On Physical and Mechanical Pr...mentioning
confidence: 65%
See 4 more Smart Citations
“…However, Srinivasan et al report that the rectilinear pattern provides higher tensile properties than concentric [195]. From the Ultrafuse 316L metal MEX tensile properties reviewed in this work, the rectilinear with 45 • /90 • pattern with appropriate printing parameters (nozzle size, printing speed, strand width, layer thickness and first layer adjustment) reported by Moritzer et al [93] provides higher tensile properties than other infill patterns [66,98] and also similar infill patterns [53,57]. As reported by Singh et al [79], the 0 • /90 • zigzag infill pattern in metal MEX can also provide comparable tensile properties to MIM parts.…”
Section: Effects Of Printing Parameters On Physical and Mechanical Pr...mentioning
confidence: 65%
“…In addition to effects on relative sintered density, Singh et al reported that an increase in the flow rate multiplier up to 120% could improve the surface quality [84]. However, as reported by Rosnitschek et al [98], a too-high flow rate multiplier (200%) results in the deformation of the printed parts because of excessive material. Regarding the layer thickness, most studies report that the thinner layer thickness leads to higher properties [56,68,73,84] due to the reduction of voids between the deposited paths.…”
Section: Effects Of Printing Parameters On Physical and Mechanical Pr...mentioning
confidence: 97%
See 3 more Smart Citations